2014
DOI: 10.1371/journal.pone.0096546
|View full text |Cite
|
Sign up to set email alerts
|

A Novel TetR-Regulating Peptide Turns off rtTA-Mediated Activation of Gene Expression

Abstract: Conditional regulation of gene expression is a powerful and indispensable method for analyzing gene function. The “Tet-On” system is a tool widely used for that purpose. Here, the transregulator rtTA mediates expression of a gene of interest after addition of the small molecule effector doxycycline. Although very effective in rapidly turning on gene expression, the system is hampered by the long half-life of doxycycline which makes shutting down gene expression rapidly very difficult to achieve. We isolated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This remarkably simple allosteric mechanism, which is likely to play a role in many other TetR-type repressors, is particularly well-suited for regulatory circuits requiring a broad inducer specificity, as it hardly places any constraints on the precise chemical nature of the ligand. Given that their specificity can be altered without affecting the allosteric mechanism, TetR-type repressors are highly attractive as molecular switches in biotechnological applications and synthetic biology [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This remarkably simple allosteric mechanism, which is likely to play a role in many other TetR-type repressors, is particularly well-suited for regulatory circuits requiring a broad inducer specificity, as it hardly places any constraints on the precise chemical nature of the ligand. Given that their specificity can be altered without affecting the allosteric mechanism, TetR-type repressors are highly attractive as molecular switches in biotechnological applications and synthetic biology [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The TetR-regulated system is a valuable tool to control gene expression both in vitro and in vivo [1–3]. Although numerous effectors have been developed for this system [12–16], only four effectors have been reported to reverse Tc-induced gene expression [12,13,16]. GR33076X, a Tc homolog is a small-molecule antagonist acting on tTA in bacterial cells, but its effect was shown only at 100- to 1000-fold higher concentration than Tc [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although TAP1 and TCP1 as TetR-regulating peptides have antagonistic activities in the presence of non-saturating amount (0.03 μM) of Dox [13], usage of the peptides is inconvenient for the TetR-regulated system because transformation of plasmids harboring the peptides and addition of IPTG are needed to express them in cells. Schmidt et al reported K79, which is a peptide switching off gene expression mediated by rtTA, but its effect was apparent only after treatment with it for 10 h [16]. Thus, antagonists with a better efficacy and a faster mode-of-action need to be developed for the TetR-regulated system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetracycline regulatory systems (Tet-on and Tet-off), which were initially found from the bacterial transcription factor Tet repressor (TetR) combined with a TetR-responsive promoter ( Berens and Hillen, 2003 ; Schmidt et al, 2014 ), have been widely applied to regulate gene expression in eukaryotes ( Baron and Bujard, 2000 ). In the Tet-off system the target gene expression is suppressed in the presence of tetracycline (Tet) or its derivative doxycycline (Dox) and can be activated by tTA, a Tet-controlled transactivator protein, binding to a Tet-responsive promoter element (TRE) in the absence of Tet or Dox ( Freundlieb et al, 1997 ; Baron and Bujard, 2000 ).…”
Section: Introductionmentioning
confidence: 99%